Pelatihan Model Pembelajaran Speaking dengan Communicative Approach Bagi Guru-Guru Bahasa Inggris di Kabupaten Lampung Selatan : INA - Bambang Setiyadi; - Mahpul; Muhammad Sukirlan; Gede Eka Putrawan (Jurnal Sumbangsih, 2021)
The speaking learning model with communicative approach has been widely adopted in various countries as a method of learning English because speaking learning with communicative approach proved effective to facilitate students actively involved in the learning process of English, especially speaking. The effectiveness / success of speaking learning by communicative approach as a way of English education in helping students improve speaking skills is evidenced by the discovery of some research tried in various countries where English as a foreign language. However, in Indonesia this method is still not popular and very few teachers or practitioners apply this method. Therefore, this community service activity aims to help English teachers in South Lampung Regency improve insight and knowledge about the development / creation of a speaking learning model based on communicative approach through training and workshops by presenting material development of task-based speaking teaching materials theoretically; and conduct simulations of the development of task-based speaking teaching materials. The results of the training showed that the participants of this training gained real efficacy is an increase in professionalism in order to be able to correct the quality of the English education process, especially speaking so that the dialogue skills of students in schools face an increase. Prolonged similar training in the future still really needs to be tried.